User fees, health staff incentives, and service utilization in Kabarole District, Uganda - Kipp Walter; Kamugisha Jimmy; Jacobs Phil; Burnham Gilbert; Rubaale Tom (The World Health Organization, 2001)
OBJECTIVE: To determine the impact of user fees on the utilization of health services in a community-based cost-sharing scheme in Kabarole District, western Uganda. METHODS: Of the 38 government health units that had introduced user-fee financing schemes, 11 were included in the study. Outpatient utilization was assessed as the median number of visits per month before and after cost sharing began. FINDINGS: After the introduction of cost sharing, overall utilization of general outpatient services, assessed by combining the data from all the participating units, dropped by 21.3%. Utilization increased, however, in facilities located in remote areas, while it decreased in those located in urban or semi-urban areas. The increased utilization in remote facilities was considered to be largely attributable to health workers' incentive payments derived from cost-sharing revenues. CONCLUSIONS: Incentive payments led the health workers to offer improved services. Other factors may also have been influential, such as an improved drug supply to health facilities and increased public identification with community projects in remote areas.